The Level of Psychological Skills and Their Relationship with the Results of the Participating Teams in the Jordanian Universities Table Tennis Championship - Telfah, Shafe’ Suleiman; Bany Saeed, Nedal Mustafa; Alja’afreh, Omar Jamil; Tilfah, Yaser Mohamad (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to identify the level of psychological skills and their relationship with the results of participating teams in the Table Tennis Championship organized by the Sports Federation of Jordanian Universities. Various variables such as gender, university, and number of playing years were considered. Methods: The study used a descriptive correlational method with a sample of 87 male and female players from the total study population of 128. Data was collected using the psychological skills inventory for sports (PSIS-R-5) adopted from M. J. Mahoney, T.J Gabriel, and T. S. Perkins. The inventory comprised 41 items distributed across six dimensions: anxiety control skills, self-confidence skills, mental match preparation, motivation, team spirit skills, and concentration skills. Data was analyzed using mean, standard deviations, frequencies, percentiles, ANOVA, and correlational statistical tests. Results: The study found that the overall level of psychological skills among players was moderate. Statistically significant differences in psychological skills were observed based on the university variable, favoring Hashemite University, and the number of years playing variable, favoring players with 11 years and above. No statistically significant differences were found based on gender. Additionally, a positive correlation was established between the level of psychological skills in all dimensions and the results of the participating teams in the championship. Conclusions: The study recommends that table tennis coaches and coaches of other racket games prioritize psychological skills training as part of their training programs. This can lead to improved performance and results for players in competitions.